J. G. Ballard: Visions and Revisions
X, 255 p.
Keywords: Providing an extensive reassessment of dominant and recurring themes in Ballard's writing, including historical violence, pornography, post 9/11 politics, and urban space, this book also engages with Ballard's 'late' modernism; his experimentation with style and form; and his sustained interests in psychology and psychopathology.